Differential thermal expansion as a cause of salt decay: literature review, experiments and modelling of micro and macro effects on Ançã limestone - Gonçalves, T. D. (2016)
Salt decay is one of the harshest, most frequent and more complex types of decay of porous materials in built heritage, including natural stones, ceramics and mortars. In this article, we address the mechanism of thermal expansion which is one of the least studied, yet most controversial, of those proposed over time to explain salt decay. We present a review of scientific literature on the topic, followed by a study of the effects of thermal expansion on a specific material, the well-known Ançã limestone. The study included experimental measurement of the linear thermal expansion coefficient of the Ançã, both in its natural state and with varying contents of sodium chloride, sodium sulphate or sodium nitrate. The results show that this coefficient: (i) is significantly higher when the stone is contaminated with salt; (ii) scales approximately with the amount of salt contained in the stone pores, regardless of the type of salt. Based on these results and on modelling of damage modes at the microscopic and macroscopic levels respectively, we conclude that thermal expansion can cause powdering, disaggregation or other types of decay consisting in internal loss of cohesion. However, it is not likely to cause exfoliation of salt loaded layers.